âArudh Haji Syukur - Hilmi, Hilmi (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2005)
This article describes syair (poetry) of H. Syukur and at his time, his poetry was used as a method to teach the sludents. The writer elaborates when this poetry is started to use, who the students are, and when it is terminated. The writer employs life historical and genealogical approach to lhis explanation. H. Syukurâs poetry consists of nuo couplets of the same rhytme in each line ending. Syaia as well as saying, has been known by Jambi s people for a long time and used as a media to teach students. It contains religious teachings, especially morality. The writer also recommends that the people in Jambi preserve his poetry for the sake of educating people in line with the recent development.